2020
DOI: 10.1038/s42003-020-1094-y
|View full text |Cite
|
Sign up to set email alerts
|

Mandarin fish (Sinipercidae) genomes provide insights into innate predatory feeding

Abstract: Mandarin fishes (Sinipercidae) are piscivores that feed solely on live fry. Unlike higher vertebrates, teleosts exhibit feeding behavior driven mainly by genetic responses, with no modification by learning from parents. Mandarin fishes could serve as excellent model organisms for studying feeding behavior. We report a long-read, chromosomal-scale genome assembly for Siniperca chuatsi and genome assemblies for Siniperca kneri, Siniperca scherzeri and Coreoperca whiteheadi. Positive selection analysis revealed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 64 publications
3
39
0
Order By: Relevance
“…It has also been reported that galectins contribute to larval development of Pacific abalone (Sandamalika and Lee, 2020), muscle development in Drosophila (Pace et al, 2002) and chick muscle (Cooper and Barondes, 1990). The Gal-3 gene in Siniperca chuatsi was significantly upregulated in groups of fish with higher growth performance, suggesting that protein glycosylation might contribute to the growth performance of S. chuatsi (He et al, 2020). In general, CaM genes and their associated kinases are involved in increased growth and anabolic functions.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that galectins contribute to larval development of Pacific abalone (Sandamalika and Lee, 2020), muscle development in Drosophila (Pace et al, 2002) and chick muscle (Cooper and Barondes, 1990). The Gal-3 gene in Siniperca chuatsi was significantly upregulated in groups of fish with higher growth performance, suggesting that protein glycosylation might contribute to the growth performance of S. chuatsi (He et al, 2020). In general, CaM genes and their associated kinases are involved in increased growth and anabolic functions.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is the first report of the gene expression of digestive enzyme in S. chuatsi larvae, the latest S. chuatsi genomics data published by our research team were used to ensure the reliability of genes [13] . Almost digestive enzyme genes expression (excepted amy and pep) were detected at hatching, it's concurrent with the digestive enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real time PCR analysis followed a modified method of Khoa et al [1] and He et al [13] For total RNA isolation, the larvae for each sampling day was homogenized in 1 ml of TRIzol™ reagent (TaKaRa, Dalian, China) in triplicate. The RNA concentration and purity were detected by nucleic acid quantifier (Thermo Scientific, Waltham city, Massachusetts, USA) ensured the OD 260 / 280 of all samples ranged between 1.8 and 2.0. cDNA synthesis was reverse-transcribed using M-MLV reverse transcriptase (TaKaRa, Dalian, China) according to the manufacturer's instructions in a final volume of 20 μl.…”
Section: Quantitative Real Time Pcr (Qrt-pcr) Analysismentioning
confidence: 99%
“…Quantitative real‐time PCR analysis followed a modified method of He et al, (2020) and Tang et al, (2020). For total RNA isolation, the larvae for each sampling day were homogenized in 1–1.2 ml of TRIzol ™ reagent (TaKaRa) in triplicate.…”
Section: Methodsmentioning
confidence: 99%